Two-dimensional transition metal halides for optical applications: impact of excitons - Regis, Natan Moreira (2024)
Two-dimensional materials have experienced rapid growth since the first exfoliation of graphene in 2004, which is an atomically thin sheet of carbon atoms exfoliated from graphite. Despite several unprecedented properties of graphene, induced by quantum confinement, it lacks a band gap that limits some optoelectronic applications. however, graphene motivates a new research field of two-dimensional materials, and their potential compositions and structures, ranging from insulators to semiconductors to conductors. The wide range of conductive behavior within the quantum confinement gives rise to distinct behaviors, including a large exciton binding energy. Excitons are quasi-particles formed by an electron-hole pair that interact through Coulomb attraction, a phenomenon present in semiconductors but more notable in low-dimensional materials due to quantum confinement, which changes the dielectric environment. However, single-particle theoretical methods, such as ground-state density functional theory, do not describe excitons because it is a many-body phenomenon. Thus, a complete characterization of the optical properties of two-dimensional materials requires going beyond a single-particle perspective. Motivated by the accomplishment of several two-dimensional materials and halide perovskites, this work explores a new class of two-dimensional materials, namely, transition metal halide (TMHs) monolayers. We initially selected potential TMHs for optoelectronics in the Computational 2D Materials Database (C2DB) and subsequently analyzed the structural, electronic, optical and excitonic properties using state-of-the-art theoretical methods to study materials such as Density Funcional Theory (DFT) calculations including relativistic and bandgap correction and the evaluation of optical properties including excitonic effect within Tight Binding (TB) Hamiltonian and by the solution of Bethe-Salpeter equation (BSE). Our calculations show that the equilibrium structure calculated by C2DB agrees with those obtained here and with other theoretical works. However, electronic properties exhibit important deviations that are not homogeneous among systems. For iinstance, we observed deviations in the bandgap values up to 17 % when considering relativistic correction and for the corrected bandgap value computed applying the scissors operator methodology. We also computed optical and excitonic properties by solving the Bethe-Salpeter equations, showing isotropic and non-isotropic light absorption among the systems. The inclusion of excitonic effects decreased the maximum light absorption when compared to the absorption coefficient without these effects and also changes in the energy region of spectra. The compositions demonstrated considerable binding energy, highlighting the importance of studying this quasi-particle in theoretical calculations. The possible heterojunctions are hardly influenced by excitonic effects; thus, evaluating possible heterojunctions must take into account exctions. Finally, we found evidence of an excitonic insulator among the systems, where the excited state are preferable than the semiconducting ground state.